Influence of inoculum-to-substrate ratio on process stability and microbial community structure in anaerobic digestion of human faecal matter - Roshita Sharma; Vanshikha Gupta; Vijai Pal; Janardan Sen; Mukesh Kumar Meghvansi; Ajay Kumar Goel (Environmental Science and Pollution Research, 2026)

Integrating Albugo candida resistance with seed quality and yield traits in Indian mustard through recombinant inbred line selection - Sushma Yadav; Arun Kumar; Anjana Goel; Ajay Kumar Thakur; Kunwar Harendra Singh; Nitish Ratan Bhardwaj; Prashant Yadav (Physiological and Molecular Plant Pathology, 2026)

Deterministic strain engineering through growth-driven stacking in twisted bilayer MoS2 - Pukhraj Prajapat; Vaibhav Kandwal; Jayalekshmi U.J.; Aditya Kushwaha; Neeraj Goel; Ajay Kumar Shukla; Govind Gupta (Chemical Engineering Journal, 2026)

Quantitative Proteomic Analysis of Serum-Derived Exosomes from Patients with and Without Human Immunodeficiency Virus–Tuberculosis Coinfection - Shweta Kushwaha; Rajbala Yadav; Roopendra Kumar; Anjana Goel; Santosh Kumar; Devendra Singh Chauhan; Ajay Vir Singh (Indian Journal of Clinical Biochemistry, 2026)

Deciphering the impact of cold-adapted bioinoculants on rhizosphere dynamics, biofortification, and yield of kidney bean across varied altitudinal zones - Amir Khan; Ajay Veer Singh; Bharti Kukreti; Deepali Tiwari Pandey; Viabhav Kumar Upadhayay; Rajeew Kumar; Reeta Goel (Science of The Total Environment, 2024)

A recombinase polymerase amplification lateral flow assay for rapid detection of Burkholderia pseudomallei, the causative agent of melioidosis - Apoorva Saxena; Vijai Pal; Nagesh Kumar Tripathi; Ajay Kumar Goel (Brazilian Journal of Microbiology, 2022)

Protein biomarker elucidation for the verification of biological agents in the taxonomic group of Gammaproteobacteria using tandem mass spectrometry - Sasikumar Sabna; Dev Vrat Kamboj; Sakshi Rajoria; Ravi Bhushan Kumar; Prabhakar Babele; Ajay Kumar Goel; Urmil Tuteja; Mahendra Kumar Gupta; Syed Imteyaz Alam (World Journal of Microbiology and Biotechnology, 2021)

Development of a rapid immunochromatographic assay for detection of surface array protein (Sap), a potent biomarker of Bacillus anthracis - Nidhi Puranik; Vijai Pal; Nagesh Kumar Tripathi; Ajay Kumar Goel (Biologia, 2020)

Genome-wide analysis of oligopeptide transporters and detailed characterization of yellow stripe transporter genes in hexaploid wheat - Anil Kumar; Gazaldeep Kaur; Parul Goel; Kaushal Kumar Bhati; Mandeep Kaur; Vishnu Shukla; Ajay Kumar Pandey (Functional & Integrative Genomics, 2019)

clpC operon regulates cell architecture and sporulation in Bacillus anthracis - Lalit K. Singh; Neha Dhasmana; Andaleeb Sajid; Prasun Kumar; Asani Bhaduri; Mitasha Bharadwaj; Sheetal Gandotra; Vipin C. Kalia; Taposh K. Das; Ajay K. Goel; Andrei P. Pomerantsev; Richa Misra; et al. (Environmental Microbiology, 2015)
Summary The clpC operon is known to regulate several processes such as genetic competence, protein degradation and stress survival in bacteria. Here, we describe the role of clpC operon in B acillus anthracis . We generated knockout strains of the clpC operon genes to investigate the impact of CtsR , McsA , McsB and ClpC deletion on essential processes of B . anthracis. We observed that growth, cell division, sporulation and germination were severely affected in mcsB and clpC deleted strains, while none of deletions affected toxin secretion. Growth defect in these strains was pronounced at elevated temperature. The growth pattern gets restored on complementation of mcsB and clpC in respective mutants. Electron microscopic examination revealed that mcsB and clpC deletion also causes defect in septum formation leading to cell elongation. These vegetative cell deformities were accompanied by inability of mutant strains to generate morphologically intact spores. Higher levels of polyhydroxybutyrate granules accumulation were also observed in these deletion strains, indicating a defect in sporulation process. Our results demonstrate, for the first time, the vital role played by McsB and ClpC in physiology of B . anthracis and open up further interest on this operon, which might be of importance to success of B . anthracis as pathogen.

Highly Expressed Recombinant SEB for Antibody Production and Development of Immunodetection System - Ranu Agrawal; Pawan Kumar Singh; Sushil Kumar Sharma; D. V. Kamboj; Ajay Kumar Goel; Lokendra Singh (Indian Journal of Microbiology, 2012)

Characterization of an Environmental Strain of Bacillus thuringiensis from a Hot Spring in Western Himalayas - Syed Imteyaz Alam; Sunita Bansod; Ajay Kumar Goel; Lokendra Singh (Current Microbiology, 2011)

Semi-nested polymerase chain reaction for detection of toxigenic Vibrio cholerae from environmental water samples - Ajay Kumar Goel; Shweta Bhadauria; Pramod Kumar; Dev V. Kamboj; Lokendra Singh (Indian Journal of Microbiology, 2007)